Analisis Potensi Angin Berbasis IoT (Internet of Things) Di Daerah Kawasan Pesisir - Amindri, Mariska Yudha; ., Yusardhi; ., Sudarti (CV. ITTC INDONESIA, 2023)
This research aims to analyze the potential of IoT (Internet of Things) based wind around coastal areas. The research method used is a literature review. Based on this, the data used was obtained from various national and international scientific articles in the form of descriptions. Wind is air that moves from areas that have high pressure to areas that have low pressure. Technological developments provide convenience for human needs. One of them is the application of Internet of Things-based technology to detect wind speed and direction. Based on information obtained from several research journals, the researchers succeeded in detecting wind speed and direction using IoT-based tools. The devices that the researchers used were microcontrollers, Android, power supplies, optocoupler sensors, and magnetic field sensors. So the tool used is designed first to detect wind speed and direction and then the information or data will be stored in a database and can be accessed via the website.